The influence of sustainable reporting and corporate governance on value of mining companies listed on the ASEAN stock exchange / Rulyanti Susi Wardhani … [et al.] - Wardhani, Rulyanti Susi; Agustina, Duwi; Indarwati, Kasifa; Ridwan, Muhammad Qomaruddin; Hasanuh, Nanu (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2022)
This research aimed to analyze how good corporate governance and sustainability reporting affected company value. The study sample were are all the mining companies listed in the ASEAN Stock Exchange from 2018-2020 with a total sample of 120 companies. Secondary data was collected from annual reports and sustainability reports of companies listed on the Indonesian Stock Exchange, Bursa Malaysia, Singapore Exchange, Philippines Stock Exchange, and Thailand Stock Exchange. This study used the regression panel of the common effects model for data analysis. The findings showed that sustainability reporting had a positive effect on company value, effective and corporate governance had no impact on company value. The two independent variables (sustainability reporting and good corporate governance) significantly affected company value of mining companies listed on the ASEAN Stock Exchange from 2018 to 2020.